Maritime Justice, Environmental Crime Prevention, and Sustainable Development Goal 14 - Conor McLaughlin; Sarah Lothian; Jade Lindley (Ocean and Society)
SDG 14 “life below water” sets targets for the conservation and sustainable use of the oceans, seas, and marine resources, however, it is increasingly evident that its targets are unachievable without strengthened state‐led maritime justice. This article examines the concept of “maritime justice” from an environmental crime perspective and explores the critical link between maritime justice and ocean crime resilience. The article addresses the relationship between maritime justice and SDG 14 and explores various approaches to progress maritime justice in order to better respond to environmental crimes at sea.